COVID-19 and Other Prevalent Diseases in Africa: A Pragmatic Approach - Ejike, Cyril Emeka (Conatus - Journal of Philosophy, 2021)
The aim of this paper is to propose that the development and legitimization of African knowledge and validation systems on a pragmatic basis, is an efficient and effective means of responding to a myriad of health problems plaguing Africans, particularly the COVID-19 pandemic. Whenever there is a novel disease outbreak, the norm is to wait for the development of scientifically proven vaccines for its treatment. However, the scientific validation of drugs is a rigorous and lengthy process, thereby inappropriate for dealing with health emergencies like the COVID-19 outbreak. The alarming rapidity with which the novel COVID-19 pandemic rages globally and decimates humanity has brought to the fore the need for Africa to look inwards in search of viable and efficient alternative approaches to the pandemic. In this paper, I examine pragmatism as a theoretical framework and relate it to proposed African epistemic and validation frameworks with a particular reference to homegrown orthodox and alternative/complementary medicines. I argue that the validation and approval of any knowledge claim based on pragmatism is a more expeditious mode of attending to COVID-19 and other prevalent diseases in Africa. The application of knowledge that brings practical success in dealing with health challenges in Africa without necessarily following rigid and lengthy scientific validation procedures will go a long way toward improving human conditions and well-being. I conclude that pragmatic considerations should ultimately inform local approval to homegrown African medicines for use in Africa.